Modeling sound absorption of micro-perforates panel using wave propagation method - Py, Muhammad Sajidin (2015)
A micro-perforated panel (MPP) absorber has been known widely as an alternative absorber to the conventional fibrous type acoustic material. The MPP system is arranged with distance from a rigid wall to provide an air gap layer. Several theoretical approaches to predict the sound absorption of the MPP have been published. In particular for the double MPPs, approximate expression for the air gap impedance is used which yields deviation in the result when it is compared with the experiment. In this study, wave propagation technique is proposed to represent the behaviour of sound incident and reflected in the MPP system. The motion of the MPP is also included in the model. The proposed models provide an attractive technique to predict the sound absorption as well as the transmission and reflection. The MPP can be set to be a solid panel by adjusting the impedance of the holes to infinity and the solid panel can be turned into a rigid wall by setting the panel impedance to infinity. The model can be applied for the single MPP and multi-layer MPPs; a stand-alone system without rigid wall as well as the system backed with a rigid wall. The results for the MPP system backed by a rigid wall then is compared with experimental data. It is found that the result from the wave propagation technique has a better good agreement with the experiment at higher frequency.